Política Nacional de Fiscalização do Conjunto CFESS/CRESS: estudo da experiência do CRESS-Alagoas - Padilha, Taciana Martins (2013)
The choice of approach to the subject was due to the degree of importance it plays in relation to studies on the National Audit of both the Federal Council of Social Service as the Regional Councils of Social Service, which were based on the perspective of its historical significance, and social dimensions of affirmative principles, regulations and policies and disciplinary and pedagogical. Its range aimed at the formation of a critical Project Ethical-Political Social Worker in their daily work, since, being well articulated, these elements express the conception of this work. In order to arrive at such an understanding, we present a brief history articulated with the Brazilian Social Services, since its genesis (decade 30) until the 2000s. This social and historical hike was necessary for people to really understand the construction and the need of the National Audit of all CFESS / CRESS under the act professional Social Worker. Thus, in the mid-90s, there is a professional able to articulate both theoretical and methodological, ethical, political and technical-operational. And it is this perspective of affirmation Project Ethical-Political Social Worker who sees the need to incorporate a conscious and critical attitude in their daily work. The National Audit Committees materializes in Guidance and Control (COFI), installed in the Regional Councils of Social Service (CRESS), leading to advances in the defense and enhancement of the profession. Through this comes the realization that allows a pop theoretical maturity, ethics, politics and art in the practice of Social Work, aimed at consolidating the Project Ethical-Political spaces socio-occupational, whose challenge to position themselves critically expressions of social issues that reiterates social inequality, to reflect the conditions ethical-political, technical, operational and theoretical-methodological. This time, our intention was to stimulate a critical discussion and reflective of the theory / practice in social and occupational spaces, bringing the pop in an attempt to (re) consider the role that policy in everyday social worker. From the methodological point of view, work desk research analyzing the reports of the deliberations of the XXVI National Meeting set CFESS / CRESS, probation and supervision of activities of the Regional Council of Pernambuco, along with literature searches using several authors such as Netto, Iamamoto, Martinelli, Bridges, and Lyra Ozanira. On the other hand, also appealed to the interview instrument oral and / or written, with the development of script open questions in order to reap the answers. After hearing them, we move to the transcript of the responses, which were read, reread and, finally, compared with calls that the National Authority. The analysis of the material sought to follow in the footsteps of qualitative research: description, thematic analysis and interpretation, noticing a gap than advocates pop with the theory / practice in the professional Social Worker